The effects of teacher nodding: exploring mimicry, engagement, and wellbeing in the EFL classroom - Kennedy, Olivia; Kuwahara, Noriaki; Noble, Tracy; Fukada, Chie (Frontiers in Education, 2024)
Introduction: This preliminary study explores teacher and student mimicry of one another's nodding in the classroom and whether it impacts teacher wellbeing. Studies have consistently demonstrated correlations between physical mimicry and various desirable outcomes, including empathy, rapport, affiliation, and personal liking. While students experiencing such emotional connections with their teachers tend to achieve more academically, teachers also benefit, showing for example, reduced stress levels. Research exploring the link between mimicry of nonverbal communication such as nodding and teacher wellbeing is limited, however. This paper reports on a pilot study that begins to address this significant gap in the literature Methods: Quantitative and qualitative methodologies were combined to gather both objective and subjective data. A Pearson correlation was undertaken to capture both immediate and delayed mimicry of nodding, and cross-correlograms produced. Teacher stress levels were measured using the ratio of the low-frequency (LF) and high-frequency (HF) heart rate power bands, which was then validated with a two-dimensional model. Next, the teacher was interviewed about her wellbeing and pedagogy while watching the video data. The results were then combined and analysed.Results and discussion: While much immediate mimicry during active teaching sessions was evident in the video data, it was not found to be at a statistically significant level. The Pearson Correlation undertaken with a one-step lag, however, showed that students consistently mimicked changes in teacher nodding rate in the following dyad activity. Cross-correlation analysis between teacher and student participants during active teaching sessions and also within student dyads during pairwork activities showed strong relationships at lags spanning 0 to 60 seconds. No statistical significance between student and/or teacher nodding and either teacher self-assessed wellbeing or physiological stress levels was found, however. This is explained first by the teacher evaluating her normal baseline state as neutral rather than positive (as was reflected by the LF/HF), and second by her physiological responses to the emotional regulation strategies of surface and deep acting. Qualitative observational data, however, indicated that teacher nodding positively influenced student comprehension, interest, and confidence, and the teacher's own professional wellbeing.